Potencial do lodo de esgoto calado como insumo agrícola para a cultura do milho em latossolo vermelho - Bremm, Roseli Regina Rambo (2005)
The sewage sludge is a by-product resulting of the sewage treatment that contains high organic matter concentration and that, properly applied, it can to supply improvements in the soil fertility. The objective of this study was to evaluate the sewage sludge agricultural potential. The experiment was accomplished in field, in the year of 2004, with randomized blocks, utilizing sewage sludge with neutralization to 50% generated in the SANEPAR Wastewater Treatment Plant, Cascavel, Paraná, Brazil, with 6 treatments: a) mineral fertilizer, b) Control (without fertilization and without sewage sludge), c) 2,5, d) 5, e) 10 and f) 15 Mg.ha-1 of dry sludge, applied to the corn culture in a dystrophic red latossol typical (LVd). Soil samples were collected before installation of experiment for chemical and heavy metal analysis. To the 20, 40, 60 and 80 days after the planting were appraised the parameters of the culture development in the field: stature and diameter of plants and number of leaves. After harvesting the production components were evaluated: length and diameter of spikes, number of useful plants and mass of grains. The soil samples were collected for evaluation of the heavy metals: copper and zinc and chemical analysis. The results were appraised for the software SISVAR.LNK version 13.0 and Minitab being accomplished with Tukey test for comparison of averages with 5% level significance. It was observed that the addition of Copper and Zinc through biossolid contributed with small increment in the tenors of x these in the soil in function of the concentration of the elements in the residue as well as the low amounts applied , and for the parameters of the culture development, the best answers were obtained in the treatments that used the sludge, when compared with the control and fertilizer mineral. For the length and diameter of spikes and mass of grains the largest averages were obtained in the 15 Mg.ha-1 of sludge treatment.